2019
DOI: 10.3390/coatings9080497
|View full text |Cite
|
Sign up to set email alerts
|

Antireflection, Superhydrophilic Nano-Porous SiO2 Coating based on Aerosol Impact Spray Deposition Technique for Solar PV Module

Abstract: In this research, silica nano-particles are deposited over the borosilicate glass and silicon wafer substrates by indigenously developed Aerosol impact deposition assembly using SiH4, oxygen, and helium as precursors. The coating process involves deionization of gases leading towards nucleation sites for silica in the presence of plasma, while tuning the pressure difference between reaction and deposition chamber controls the coating thickness, porosity, and refractive index. The deposited coating layer on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Researchers compared and evaluated the impact of self-cleaning coatings on photovoltaic panel power generation. They found that PV modules coated with self-cleaning coatings lost 2.5% of their power output per day, while modules that were uncoated lost 3.3% per day [10,85,86].…”
Section: Self-cleaning Coatingsmentioning
confidence: 99%
“…Researchers compared and evaluated the impact of self-cleaning coatings on photovoltaic panel power generation. They found that PV modules coated with self-cleaning coatings lost 2.5% of their power output per day, while modules that were uncoated lost 3.3% per day [10,85,86].…”
Section: Self-cleaning Coatingsmentioning
confidence: 99%
“…It was demonstrated that the wettability is an important property of the coating because it can have an important impact on the coating durability during its use [36,37]. Furthermore, it was proven that a hydrophobic coating can be achieved by using a lowsurface-energy material to modify a rough surface [38].…”
Section: Contact-angle Measurementsmentioning
confidence: 99%
“…While possibly less critical in the buildingintegrated PV sector, these phenomena become relevant in a large number of novel potential LSC applications [1] with typical working environments in which dew formation is very common and might strongly impact on device performance. As observed on the sister PV technology, [29][30][31][32][33][34] a significant decay of LSC performance is to be expected in these conditions owing to the reduced absorption efficiency and photon trapping efficiency of the waveguide.…”
Section: Introductionmentioning
confidence: 99%